What makes a productive Russian firm? - Wildnerova, Lenka,Blöchliger, Hansjörg (OECD, 2019)
Productivity in Russia has fallen steadily over the past 15 years. This paper explores micro-level data to understand the contribution of individual firms to aggregate productivity. Overall, firm-level data corroborate the decline in aggregate productivity and a widening productivity gap against several European countries. They also show that the gap between “the best” and “the rest” has widened in Russia, similar to other countries. Russian markets are quite concentrated, i.e. dominated by few large firms. Larger firms tend to be more productive, but firms at the productivity frontier have become smaller and younger over time, suggesting that more support for young and innovative firms could help raise productivity. Foreign ownership is associated with higher productivity, and there is evidence that foreign firms generate positive productivity spillovers for domestic firms. Service firms belong to the most productive, yet the service sector remains underdeveloped. Mining is also very productive but less than in other countries. Differences in productivity across regions are large, even controlling for many other determinants, suggesting a lack of capital and labour mobility and knowledge transfer across regional borders.
10.1787/8590f752-en
Keywords: Amtsdruckschrift; Graue Literatur; Economics; Russian Federation; Russian economy; firm-level productivity; industrial organisation; productivity gap; privatisation; foreign ownership; regional productivity differences; entry and exit offirms